Capacity building of security officers through IVMS CCTV application training - Very Kurnia Bakti; Dairoh Dairoh; Rivaldo Mersis Brilianto (Universitas Muhammadiyah Magelang, 2022)
Knowledge of CCTV observation using the IVMS CCTV application is critical in order to accurately and quickly support the monitoring and security process by utilizing mobile phones. At the Politeknik Harapan Bersama, a total of 17 security officers received training on how to use the IVMS application to assist security officers in monitoring conditions on campus. Participants learn about the fundamentals of CCTV, the IVMS CCTV application, and then get hands-on practice and assistance in using the application. The security officers were very enthusiastic and could understand and use the application well, from logging in to processing recorded data on CCTV with the IVMS application.